EDUCATION AND OBESITY PREVENTION THROUGH HEALTHY LIFESTYLES - Prasiwi, Nikita; Tysa Runingsari (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2025)
Background: Obesity is one of the significant public health problems in Indonesia, with an increasing prevalence due to unhealthy diet, low physical activity, and hormonal factors. This disease increases the risk of degenerative diseases such as diabetes mellitus, hypertension, and cardiovascular disease. As a preventive measure, health education was held with the theme "Education and Prevention of Obesity Through Healthy Diet and Healthy Lifestyle" aimed at female participants. Method: The activity began with a pre-test to measure initial knowledge, then the delivery of materials and the last post-test was carried out in Pucangan Village, Montong District with 25 participants. Result: There was an increase in knowledge from the results of providing education related to obesity. The results of the BMI calculation showed 11 people with obesity, Conclusion: Increasing knowledge about obesity prevention can be done by providing education. Continuous efforts are needed to prevent obesity.